KONSEP PERTUMBUHAN DAN PERKEMBANGAN - Ainun Jariyah; Paulus Rudirudolof Ekaputra; Tiara Novianti Dadi Lado; Maria Nggara Jaru Da Jeen; Beata Maria Suryanika Tonda; Novensianus Lera Boleng; Yohanes Mari Ba’i Leta (Jurnal Bionatural, 2025)
This article discusses the concepts of growth and development in the context of learner development. Growth and development are two interrelated processes that occur throughout a human's life, beginning from the prenatal stage to adulthood. Growth refers to quantitative physical changes, such as increases in body size and tissue mass, while development focuses on qualitative functional changes, including cognitive, emotional, motor, and social aspects. A deep understanding of these two concepts is essential for educators, healthcare professionals, and parents to support the optimal development of learners. This article also explores various factors that influence growth and development, such as genetics, nutrition, environment, and stimulation. Understanding the differences between growth and development, along with the influencing factors, has significant implications for designing age-appropriate educational approaches and for the early detection of developmental disorders. Through a comprehensive approach, it is hoped that the growth and development processes of learners can proceed optimally.